The Relationship Of Tiktok Content Trends Regarding Tourism Travel To The Travel Interest Of Garut University Students - Wufron, Wufron; Lestari, Amik Ayu; Nursifa, Dea (Jurnal Wacana Ekonomi, 2025)
This study aims to analyze the influence of TikTok content trends regarding travel on the travel interest of Garut University students. This study uses a quantitative approach method by examining the correlation of spearman rank with SPSS 26 data processing tools. The spearman rank correlation test is used to measure the relationship between two ordinal or interval variables. The test results showed a value of 82.5%, which means that there is a very strong relationship with a range between 80% - 100% between TikTok content trends regarding travel and travel interest of University of Garut students. With a sig value. 0.000 which is smaller than the alpha value of 0.05 indicates a positive relationship between TikTok content and the interest in traveling for University of Garut students.